Modification of EBV-Associated Pathologies and Immune Control by Coinfections - Münz, Christian (Frontiers in Oncology, 2021)
The oncogenic Epstein Barr virus (EBV) persistently infects more than 95% of the human adult population. Even so it can readily transform human B cells after infection in vitro, it only rarely causes tumors in patients. A substantial proportion of the 1% of all human cancers that are associated with EBV occurs during co-infections, including those with the malaria parasite Plasmodium falciparum, the human immunodeficiency virus (HIV) and the also oncogenic and closely EBV related Kaposi sarcoma associated herpesvirus (KSHV). In this review I will discuss how these infections interact with EBV, modify its immune control, and shape its tumorigenesis. The underlying mechanisms reveal new aspects of EBV associated pathologies and point towards treatment possibilites for their prevention by the human immune system.